2002
DOI: 10.1177/154411130201300503
|View full text |Cite
|
Sign up to set email alerts
|

Oral Lichen Planus and Malignant Transformation: Is a Recall of Patients Justified?

Abstract: There has been a continuous debate regarding the possible malignant potential of oral lichen planus (OLP). Based on the results from follow-up studies, OLP is regarded by several authors as a pre-malignant condition, and patients with OLP have been recommended to have their lesions monitored two to four times annually. This recommendation needs reconsideration, because a recall system of all patients with OLP requires substantial economic resources. In a reality where such resources are limited, a recall syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(52 citation statements)
references
References 69 publications
1
48
2
1
Order By: Relevance
“…In our study, complete remission was observed in 66.7% (n=10) and partial remission in 33.4% (n=5) of patients after eight weeks of treatment with prednisolone 40 mg/day along with tapered doses, which was more or less similar to the results reported by Carbone M et al [24] A double blind placebo controlled randomized clinical trial conducted by Saawar N et al [6] transformation (up to 0.2-2%) as compared to another forms. [25,26] Therefore, it may be presumed that lycopene and prednisolone may decrease the risk of malignant transformation in OLP.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, complete remission was observed in 66.7% (n=10) and partial remission in 33.4% (n=5) of patients after eight weeks of treatment with prednisolone 40 mg/day along with tapered doses, which was more or less similar to the results reported by Carbone M et al [24] A double blind placebo controlled randomized clinical trial conducted by Saawar N et al [6] transformation (up to 0.2-2%) as compared to another forms. [25,26] Therefore, it may be presumed that lycopene and prednisolone may decrease the risk of malignant transformation in OLP.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of malignant potential has been controversial, possibly due to a wide range of reported incidences of 0%-12.5% (16,17). Further studies are needed to better predict OLP patients who are at risk of developing oral squamous cell carcinoma (OSCC).…”
Section: Discussionmentioning
confidence: 99%
“…The malignancy of OLP has been controversial with malignant transformation rates ranging from 0.2% up to 12.5%, these rates being up to 60 times higher as compared to the general population (13,16,17). The malignant transformation of OLP lesions has been attributed to both intrinsic (inflammation mediators) and extrinsic factors (18).…”
Section: Introductionmentioning
confidence: 99%
“…Whether OLP has a premalignant potential is a matter of discussion. The reported transformation incidence to oral cancer changes from 0-9% (14). For this reason, a clinical follow-up of patients with OLP, including repeated biopsies of recurrent or recalcitrant lesions is recommendable for any treatment (12,15).…”
Section: Discussionmentioning
confidence: 99%